Involvement of neurokinin-1 receptors in the autonomic nervous system in colorectal distension-induced cardiovascular suppression in rats - Kurogochi, Kentaro; Uechi, Masami; Orito, Kensuke (Frontiers in Pharmacology, 2022)
Situational syncope, which includes rectally mediated reflexes, is defined as syncope induced by a specific situation. Its pathogenesis generally involves disorders of the autonomic nervous system. However, the mechanisms and preventive strategies are not yet well understood. Therefore, we hypothesized that a tachykinin neurokinin-1 receptor might be involved in the autonomic nervous system, and that a neurokinin-1 receptor antagonist could mitigate reflex syncope. This study used a rat model in which the reflex was induced by afferent vagal stimulation with colorectal distension (CRD). In the study, the rats were divided into three groups: non-CRD, CRD, and CRD with a neurokinin-1 receptor antagonist. First, we examined the effect of fosaprepitant, a neurokinin-1 receptor antagonist, on the circulatory response in this model. We then determined the brain regions that showed increased numbers of c-Fos immunoreactive cells in the respective groups. Our results suggest that the colorectal distension procedure reduced blood pressure and that fosaprepitant lowered this response. In addition, the number of c-Fos immunoreactive cells was increased in the caudal ventrolateral medullary region with colorectal distension, and this number was decreased by the administration of fosaprepitant. In conclusion, fosaprepitant might be involved in the vagal reflex pathway and potentially suppress the circulatory response to colorectal distension.